Repercussions in brain hemispheres integration with image and text, through the use of information technology and paintings in their steps fractals (2015)
ABSTRACT: "We are wasting over 200 million nerve fibers that connect our hemispheres and can instantly perform simultaneous functions we want it, if we do not change our educational system and our cultural ways people will end up with “Split brain”. It is important to develop methodologies that encourage various features found in our brain hemispheres. A creative person is the one who can process information in different ways, sensorial data we receive. The fact of having a dominant hemisphere primarily the right or left involves a change in the learning style. An aware teacher about this topic will develop activities to stimulate the two hemispheres in order to keep the attention of his or her student and never miss motivation."